Resilience and its association with post-traumatic stress disorder, anxiety, and depression symptoms in the aftermath of trauma: A cross-sectional study from Nepal - Saraswati Dhungana; Rishav Koirala; Saroj Prasad Ojha; Suraj Bahadur Thapa (Elsevier, 2022)
Background: Resilience is a multidimensional construct. Despite its importance as protective against psychiatric disorders, it remains largely unexplored in context of Nepal. We investigated the role of resilience in the development of various psychiatric symptoms as post-traumatic stress disorder, anxiety and depression following trauma in clinical population in a psychiatry outpatient. Methods: We interviewed one hundred patients who sought treatment in psychiatry outpatient of Tribhuvan University Teaching Hospital in Kathmandu, Nepal. The sampling strategy was purposive and inclusion criteria were 18-60 years and trauma history. We used the World Health Organization Composite International Diagnostic Interview version 2.1 for trauma categorization, the Post-Traumatic Stress Disorder Checklist-Civilian version to measure the post-traumatic stress disorder symptoms, and the 25-item Hopkins Symptom Checklist-25 to assess the level of anxiety and depression symptoms. We used Nepali adapted resilience scale derived from the original Wagnild and Young Resilience scale to measure resilience. We investigated the associations between resilience scores and the scores on depression, anxiety and post-traumatic stress disorder using bivariate and multivariate analysis. We adjusted for trauma type, socioeconomic status, employment, marital status and gender in the final models. Results: Resilience was found to have negative relation with post-traumatic stress disorder, anxiety, and depression symptoms even after adjusting for other important factors in patients with trauma in the final multivariate analysis. Conclusion: Resilience was independently and negatively related with symptoms of post-traumatic stress disorder, anxiety, and depression in patients with history of trauma presenting to the hospital. Interventions aiming to promote resilience in trauma patients might be effective in reducing psychiatric symptoms such as stress disorder, anxiety and depression. Prospective studies using more robust measures of resilience combining personal attributes to social support systems, across different settings in trauma population should be the focus of future research.